Failure investigation of an underground low voltage XLPE insulated cable. Issue 5 (7th September 2015) - Ul-Hamid, Anwar; Soufi, Khaled Y.; Al-Hadhrami, Luai M.; Shemsi, Ahsan M.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to determine the effect of exposure of underground electrical cables to chemically contaminated water. Design/methodology/approach – Visual inspection and photography were carried out to record the appearance of electrical cables. Failed and un-failed cable samples were collected and analyzed using light microscopy, scanning electron microscopy coupled with energy-dispersive X-ray spectroscopy and Fourier transform infrared spectroscopy. Sand and water samples were chemically tested for contaminants. Findings – Underground low-voltage 0.6/1-kV cross-linked polyethene insulated cables belonging to a chemical production plant suffered failure after four years of service. Excavation of the cable trench revealed that the cables were buried in sand polluted with chemically contaminated water. The cables were discolored and covered with corrosion deposits. Experimental results indicated that the cable insulation was heavily degraded and the outer jacket of polyvinyl chloride exhibited cracks that had penetrated through its thickness. Water and sand surrounding the cable were found to have high concentrations of ammonia. Mechanical testing of the cables indicated high values of stiffness that could contribute to the formation of cracks at the surface. Practical implications – It was concluded that contamination in the water had degraded the cable, resulting in the development of a network of branched cracks within the cable insulation through which water could permeate, leading to eventual failure of the cable. Accelerated degradation took place due to exposure to the contaminated environment, which promoted aging and brittleness. Continued exposure of electric cables to contamination would lead to power failures and plant shutdowns. Originality/value – This paper provides an account of a failure investigation of low-voltage electrical cable buried underground. It discusses the role of contaminated environment in the eventual failure of electrical cable due to corrosion. This information will be useful for plant engineers and project managers working in any industry that makes use of chemicals.